Anisotropic strain: A critical role in domain evolution in (111)- Oriented ferroelectric films. (March 2019) - Zou, M.J.; Tang, Y.L.; Zhu, Y.L.; Feng, Y.P.; Wang, Y.J.; Han, M.J.; Zhang, N.B.; Ma, J.Y.; Wu, B.; Ma, X.L.
Abstract: Domain behavior of (111)- oriented perovskite ferroelectric films is significantly different from (001)-/(101)- oriented ones, resulting in enhancing property responses such as a superior susceptibility and a reduced coercive field. However, the domain structures and evolutions with the thickness of (111)-oriented ferroelectric films, which are crucial to further understand the distinctive properties, are still obscure. In this study, the ferroelectric domains of (111)- oriented PbTiO3 films are investigated by transmission electronic microscopy (TEM) and piezoresponse force microscopy (PFM). We identify the domain evolution with the film thicknesses under anisotropic strains imposed by the orthorhombic GdScO3 (101)O substrates. Contrast analysis and electron diffraction patterns reveal that only four ferroelectric variants evolve in PTO films: d2 +, d2 -, d3 + and d3 -, with the polarization directions along [010], [0 1 ¯ 0], [001] and [00 1 ¯ ], respectively. Two kinds of domain walls are formed: "inclined" (011) domain walls for d2 - /d3 + (d2 + /d3 - ) domains, "normal" (01 1 ¯ ) domain walls for d2 - /d3 + (d2 + /d3 - ) domains. The width of periodically distributed d2 + /d3 + (d2 - /d3 - ) domains increases with film thickness following the square root rule. Aberration-corrected scanning transmission electronic microscopy demonstrates the lattice characteristics of domains in (111)- oriented PbTiO3 films are consistent with tetragonal ferroelectric domains. PFM studies reveal that both the out-of-plane and in-plane polarization components of d2 - /d3 + (d2 + /d3 - ) domains are non-identical, whereas the d2 + /d3 + (d2 - /d3 - ) domains possess uniform out-of-plane polarization component and non-uniform in-plane polarization component. This study discloses the domain structure in (111)- oriented tetragonal ferroelectric films under anisotropic strains and the association with the ferroelectric properties. Graphical abstract: Image 1